2005
DOI: 10.1111/j.1399-543x.2005.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Slowly progressing form of type 1 diabetes mellitus in children: genetic analysis compared with other forms of diabetes mellitus in Japanese children

Abstract: HLA phenotypes and genotypes in patients with IDDMS were different from those in NIDDM and control subjects and were closer to those of IDDMA. Together with a low prevalence of HLA-A24, the genetic features are similar to those of SPIDDM and latent autoimmune diabetes in adults (LADA) in adults. In our series, the clinical features such as lack of obesity and lack of responsiveness to oral hypoglycemic agents were most different from those of adults' onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
1
23
1
Order By: Relevance
“…It is reported that 81.8% of the Japanese with idiopathic T1D (B0 + B1 areas) possess the HLA DRB1*0405 allele compared to the 58.8% with autoimmune T1D (Urakami et al, 2002 (Thomson et al, 2007), but is rare in the Japanese. Conversely, the DR8 haplotype confers susceptibility to Japanese T1D (Awata et al, 1992;Kawabata et al, 2002;Kobayashi et al, 1993;Murao et al, 2004;Ohtsu et al, 2005;Yasunaga et al, 1996) and is present only in Japanese and Korean T1D (Thomson et al, 2007). However, some studies have found no evidence that the DR8 haplotype confers susceptibility to Japanese T1D (Maruyama et al, 1994;Murao et al, 2004;Tanaka et al, 2002).…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 90%
See 4 more Smart Citations
“…It is reported that 81.8% of the Japanese with idiopathic T1D (B0 + B1 areas) possess the HLA DRB1*0405 allele compared to the 58.8% with autoimmune T1D (Urakami et al, 2002 (Thomson et al, 2007), but is rare in the Japanese. Conversely, the DR8 haplotype confers susceptibility to Japanese T1D (Awata et al, 1992;Kawabata et al, 2002;Kobayashi et al, 1993;Murao et al, 2004;Ohtsu et al, 2005;Yasunaga et al, 1996) and is present only in Japanese and Korean T1D (Thomson et al, 2007). However, some studies have found no evidence that the DR8 haplotype confers susceptibility to Japanese T1D (Maruyama et al, 1994;Murao et al, 2004;Tanaka et al, 2002).…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 90%
“…Even if the mean onset age is older than 30 years old, this haplotype appears to confer susceptibility to rapid-onset T1D with slow-onset T1D (which includes both A1 and A2 areas) (Katahira et al, 2008;Takeda et al, 2002). However, there are no studies reporting that this haplotype confers susceptibility to slow-onset T1D (which includes A2 area and excludes A1 area) even if the mean onset age is young (Kobayashi et al, 1993;Maruyama et al, 1994;Murao et al, 2004;Ohtsu et al, 2005). The effects of DRB1*04 subtypes on the DQA1*03:01-DQB1*03:02 haplotype vary from susceptibility to T1D (DRB1*04:01, *04:02, or *04:05) to protection against T1D (DRB1*04:03 or *04:06).…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 90%
See 3 more Smart Citations